Astrocytic expression of the RNA regulator HuR accentuates spinal cord injury in the acute phase. (9th June 2017) - Kwan, Thaddaeus; Floyd, Candace L.; Patel, Jason; Mohaimany-Aponte, Amanda; King, Peter H.
Highlights: Transgenic HuR in astrocytes (Tg-HuR) translocates to the cytoplasm in spinal cord injury (SCI). Tg-HuR mice have decreased neuronal survival in acute SCI. Tg-HuR mice have increased astrocyte activation and vascular permeability in acute SCI. Abstract: We recently showed that the RNA regulator, HuR, is translocated to the cytoplasm in astrocytes in the acute phase of spinal cord injury (SCI), consistent with its activation. HuR positively modulates expression of many pro-inflammatory factors, including IL-1β, TNF-α, and MMP-12, which are present at high levels in the early phase of SCI and exacerbate tissue damage. Knockdown of HuR in astrocytes blunts expression of these factors in an in vitro stretch injury model of CNS trauma. In this report, we further investigate the impact of HuR in early SCI using a mouse model in which human HuR is transgenically expressed in astrocytes. At 24 h following a mid-thoracic contusion injury, transgenic HuR translocated to the cytoplasm of astrocytes, similar to endogenous HuR, and consistent with its activation. Compared to littermate controls, the transgenic mice showed a global increase in astrocyte activation at the level of injury and a concomitant increase in vascular permeability. There was a significant decrease in neuronal survival at this time interval, but no differences in white matter sparing. Long term behavioral assessments showed no difference in motor recovery. In summary, transgenic expression of HuR in astrocytes accentuated neuronal injury and other secondary features of SCI including increased vascular permeability and astrocyte activation. These findings underscore HuR as a potential therapeutic target in early SCI.